HUBUNGAN PERSEPSI GURU TERHADAP HUMAN RELATION KEPALA SEKOLAH DENGAN MOTIVASI BERPRESTASI GURU TAMAN KANAK-KANAK SE-KECAMATAN TAMPAN KOTA PEKANBARU - Meyke Garzia; Zulkifli N '; Devi Risma (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The aim of this research is to know whether there is correlation between teacher’s perception of the human relations school principal and achievement motivation of kindergarten’s teachers at Tampan District of Pekanbaru City. The population of this research is kindergarten’ s teachers at Tampan District of Pekanbaru City that consists of 123 teachers, the samples of this research are 55 teachers which taken by using Slovin formula. Method of this research is Pearson Product Moment correlation to know the correlation between Teacher’s Perception of the Human Relations School Principal and Achievement Motivation. The technique of collecting data used questioner in Likert scale form. The technique of analyzing data used scale test and statistic analytical by using SPSS program for Windows Ver. 17. Based on hypothesis there is any significant positive correlation between teacher’s perception of the human relations school principal and achievement motivation of kindergarten’s teachers at Tampan District of Pekanbaru City. It could be seen from the result of correlation coefficient that 0,488 and significant level is 0,01<0,05. The level of correlation between teacher’s perception of the human relations school principal and achievement motivation of kindergarten’s teachers is in the middle category with the rank of determinant coefficient in the amount 23,8%, it means that teacher’s perception of the human relations school principal affect achievement motivation as much as 23,8%.Keywords: Perception, Human Relations, Achievement MotivationRELATIONS SCHOOL PRINCIPAL AND ACHIEVEMENT THE CORRELATION TEACHERS PERCEPTION OF THE HUMAN Meyke Garzia, Zulkifli N, Devi Risma